Comparison of the H(+)/ATP ratios of the H(+)-ATP synthases from yeast and from chloroplast - Petersen, Jan (National Academy of Sciences, 2012)
F(0)F(1)-ATP synthases use the free energy derived from a transmembrane proton transport to synthesize ATP from ADP and inorganic phosphate. The number of protons translocated per ATP (H(+)/ATP ratio) is an important parameter for the mechanism of the enzyme and for energy transduction in cells. Current models of rotational catalysis predict that the H(+)/ATP ratio is identical to the stoichiometric ratio of c-subunits to β-subunits. We measured in parallel the H(+)/ATP ratios at equilibrium of purified F(0)F(1)s from yeast mitochondria (c/β = 3.3) and from spinach chloroplasts (c/β = 4.7). The isolated enzymes were reconstituted into liposomes and, after energization of the proteoliposomes with acid–base transitions, the initial rates of ATP synthesis and hydrolysis were measured as a function of ΔpH. The equilibrium ΔpH was obtained by interpolation, and from its dependency on the stoichiometric ratio, [ATP]/([ADP]·[P(i)]), finally the thermodynamic H(+)/ATP ratios were obtained: 2.9 ± 0.2 for the mitochondrial enzyme and 3.9 ± 0.3 for the chloroplast enzyme. The data show that the thermodynamic H(+)/ATP ratio depends on the stoichiometry of the c-subunit, although it is not identical to the c/β ratio.